An Online-Based Food Ordering System for T&K Eatery in Ughelli North Delta State Nigeria - Favour Edafeajiroke, Michael; Edevbie Agboje, Oboyerulu; Kayode Saka, Kamil (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2025)
Information technology, particularly online ordering platforms, has enabled small businesses to compete effectively with larger ones by automating processes. However, existing methods often face inefficiencies such as long wait times, lack of meal information, excessive printing, staff fatigue, and poor delivery. Efforts were made to automate the ordering process to address these challenges and improve profitability, market share, and customer satisfaction. Utilizing the SDLC methodology, existing systems were evaluated, and data was collected through interviews. A new system was developed and modeled using data flow diagrams, with implementation leveraging MySQL, PHP, HTML, CSS, and JavaScript due to their simplicity, open-source nature, and cross-platform support. The food ordering system was tested over two months with twenty customers at T & K Eatery, resulting in significant improvements: Customer Satisfaction increased from 60% to 95%, Speed of Service improved from 50% to 80%, and Order Accuracy rose from 55% to 93%. Additionally, the Average Order Completion Time was reduced by 46.7%, and the Error Rate decreased by 83.3%. These results, validated through statistical analysis, highlight the system’s effectiveness in enhancing operational efficiency and customer satisfaction.